The policy of the International Olympic Committee on gender equality in Olympic sport - Vorobiova, A.; Keller, M.; Vasylenko, M. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: With the revival of the Olympic Games (OG) in 1896, the IOC opposed allowing women to compete. However, over time, women were admitted to competitions due to socio-cultural influences (including strong influence of feminist organizations) [1]. Nowadays the OG have become one of the biggest global platforms for advancing gender equality in sport (after launching the Gender Equality Review Project in 2017) [2], but some current developments need to be critically discussed. The aim of this study was to discuss the impact of IOC policies on the development of womens sports in the world and the problems that arise in this regard.